2020
DOI: 10.1016/j.nucmedbio.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of peptide-based imaging agents [68Ga]Ga-PSMA-11, [68Ga]Ga-AMBA, [68Ga]Ga-NODAGA-RGD and [68Ga]Ga-DOTA-NT-20.3 in preclinical prostate tumour models

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Zhang-Yin et al [37] Pre-clinical 68 Ga-AMBA GRPR 68 Ga-AMBA showed good tumor uptake, high tumor-to-background contrast using PC3 cell line.…”
Section: Year Type Of Study Radiotracer Target Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang-Yin et al [37] Pre-clinical 68 Ga-AMBA GRPR 68 Ga-AMBA showed good tumor uptake, high tumor-to-background contrast using PC3 cell line.…”
Section: Year Type Of Study Radiotracer Target Commentmentioning
confidence: 99%
“…The first studies regarding the use of GRPRs for PET/CT imaging and treatment of prostate cancer were based on radiolabelled GRPR-agonists, such as 68 Ga-AMBA/ 177 Lu-AMBA. 68 Ga-AMBA showed, in mice xenografted with 22Rv1 prostate cancer cell line, good tumor uptake, and a high tumor-to-background ratio according to Zhang-Yin et al [ 37 ]. In another study 55 Co-NOTA-AMBA in PC3 xenografted mice was superior for PET/CT imaging, compared to 68 Ga-NOTA-AMBA since it showed a better tumor-to-organ ratio [ 38 ].…”
Section: Theranostic Pet Tracersmentioning
confidence: 99%
“…Even more octamer peptides have been studied with other isotopes, with similar good-but-not-superior results [ 134 , 135 , 136 ]. Cyclic mono or multimeric peptides, labelled with 68 Ga through a chelator, may also prove to have a future, although a head-to-head clinical comparison is still missing [ 57 , 137 , 138 , 139 , 140 ]. Using the chelator as a positive concept in the RGD structure, some researchers even head back to 18 F and investigate 18 F-labelled NOTA-RGD variants [ 141 ].…”
Section: Direct Targeting Of Angiogenesismentioning
confidence: 99%
“…One such target is neurotensin receptor1 (NTSR1), which exhibits high or moderate expression in 92% of PC tumors, including all PSMA-negative tissues, suggesting a potential complementary role in targeted imaging or/and therapy [ 60 ]. Although the value of NTSR1 expression was not assessed in patients with PSMA-negative PET/CT, preclinical in vitro and in vivo studies in PC animal models suggest that PET imaging using specific probes for NTSR1, such as 68 Ga-DOTA-NT-20.3 or 18 F-DEG-VS-NT could represent viable alternative options for selecting therapies targeting NTSR1 in mCRPC patients with limited PSMA expression levels [ 60 , 61 ].…”
Section: Molecular Biomarkersmentioning
confidence: 99%